2018
DOI: 10.1002/er.4320
|View full text |Cite
|
Sign up to set email alerts
|

Optical study of twin-tanked ICS solar heaters combined with asymmetrical CPC-type reflectors

Abstract: Summary The distribution of solar irradiance on the absorbing surface of a typical integrated collector storage (ICS) system combined with reflector troughs is commonly studied by means of ray tracing techniques. A conceptually different alternative is offered by the method of the average number of reflections (ANR). In the present work, the latter is employed for the systematic optical study of realistic ICS models. In all cases, the solar devices consist of twin cylindrical storage tanks which are mounted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Souliotis et al 20 used ray tracing techniques to study the distribution of solar irradiance on the absorbing surface of an ICS system. Their results showed that the optical efficiency varied in the range of 0.75-0.91.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Souliotis et al 20 used ray tracing techniques to study the distribution of solar irradiance on the absorbing surface of an ICS system. Their results showed that the optical efficiency varied in the range of 0.75-0.91.…”
Section: Introductionmentioning
confidence: 99%
“…For the Integrated Collector Storage Solar Water Heater (ICSSWH), several studies 15–19 have been conducted to show its performances with respect of other existing and well marketed technologies. Souliotis et al 20 used ray tracing techniques to study the distribution of solar irradiance on the absorbing surface of an ICS system. Their results showed that the optical efficiency varied in the range of 0.75–0.91.…”
Section: Introductionmentioning
confidence: 99%
“…Many other scholars (Zacharopoulos et al, 2000;Zacharopoulos, 2001;Sarmah et al, 2011;Yurchenko et al, 2015;Ustaoglu et al, 2016;Paul, 2019) employed elaborate simulations that consider Fresnel formulas, optical properties of air, transparent media, and specular properties of reflector surfaces. Others (Rabl, 1976b;Souliotis and Tripanagnostopoulos, 2008;Souliotis et al, 2019) performed detailed optical assessments of CPCs through a theoretical evaluation of Average Number of Reflections (ANR) as an alternative to the ray tracing approach. Zacharopoulos et al (1996) performed optical analysis of four different absorber-envelope configurations in a CPC using a ray tracing model (RTM).…”
Section: Introductionmentioning
confidence: 99%